Analysis of Adverse Reactions of Cosmetics in Chinese Han Population in Recent Five Years - Dong C; Liu F; Liao Z; Lin L; Wang R; Du J; Huang W (Dove Medical Press, 2023)
Canbin Dong,1,* Fang Liu,1,* Zuda Liao,2 Lanmei Lin,1 Runnan Wang,1 Juan Du,1 Wen Huang1 1Department of Dermatology, Huashan Hospital, Fudan University, Shanghai Institute of Dermatology, Shanghai, People's Republic of China; 2Medical Insurance Office of Huashan Hospital Affiliated, Fudan University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Juan Du; Wen Huang, Department of Dermatology, Huashan Hospital, Fudan University, Shanghai Institute of Dermatology, Shanghai, 200040, People's Republic of China, Tel +86-21-52889999, Fax +86-21-52887782, Email dujuan@huashan.org.cn; huangwen2@huashan.org.cnBackground: There are still some gaps in the summary and generalization of cosmetic-related adverse reaction reports.Objective: The aim of this study is to summarize and analyze the occurrence of cosmetic adverse reactions in Shanghai Han population by using available survey data.Materials and Methods: Collection, statistics and analysis of patients with cosmetic adverse reactions in Shanghai Huashan Hospital from 2017 to 2021.Results: Among the 1004 patients, most of them (96.71%) were diagnosed as cosmetic contact dermatitis, which often occurred within 3 days of using cosmetics (51.79%). A total of 260 patients were tested with patch test, but the compliance rate was only 18.08%. Among them, 240 patients underwent additional European standard allergen tests, and positive allergens were detected in 210 cases (87.5%). Univariate analysis revealed that dosage form (emulsion and cream), age (≤ 25 years) and the allergic ingredients triethanolamine, rose oil, propylene glycol, thiomersal and musk ambrette are associated with the occurrence of cosmetic adverse reactions within seven days. A logit prediction model was also successfully constructed: Logit (P) = 1.710- 0.796× 1 + 1.185× 2 − 3.650X3-1.335X4.Conclusion: This study complements the data reported on cosmetic adverse reactions in the Chinese Han population and suggests that in future clinical diagnosis and data collection, emphasis should be placed on patch testing, combining the patch test with cosmetic protoplast with the European standard allergen test to improve the detection rate.Keywords: adverse reaction reporting, cosmetics, contact dermatitis, personal care products, patch tests